Responsabilidade por verbas trabalhistas na terceirização de mão-de-obra. - Cabral, Arleide Lucena (2004)
The present work delineates the preponderant lines of the responsibility for work budgets for occasion of not execution of the contract or illicitness in the relationships in the ambits private and public. Initially it is about studying the phenomenon tertiary inserted in the globalization, checking that the tertiary practices are instruments of fiexibilization of the work relationships, by virtue of the increase of the international competitiveness and of the consequent search of reduction of costs for the companies. It was possible, to verify some foreign systems that identify the tertiary practices. It was verified, also, that many civil institutes and commercial in Brazil are tertiary manifestations with reflexes in the ambit of work, by virtue of the proximity among the contracts of labor tertiary and that of services and products. On the other hand, it was evidenced that from the Law 6.019/74, the legislator worried in attributing responsibility for work budgets to the receiver of services, but in a very restricted way. Later, the Statement 256/TST also enlarged such responsibility to the hypothesis of illicit tertiary practice, being reformed by the Statement 33 1/TST, that still extended more the responsibility for work budgets, reaching the licit tertiary practice, for the simple not greed of the boss, independently of recognition of the employment entail between worker and receiver of services or of the bankruptcy of the company vendor of services. In the public ambit, discusses that responsibility, because the Law 8.666/93 doesn't admit the responsibility, although the Resolution 96/00 of TST, extend it to the state entities. Finally, it can be concluded that the extension of the responsibility for work budgets in the tertiary relationships is a controversial question, by virtue the normative lack in disharmony with the intensity of the practical tertiary in the labor market, mainly with relationship to the state entities.